2024
DOI: 10.3390/jcm13020427
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Transcutaneous Electrical Nerve Stimulation (TENS) on Acute Pain and Other Postoperative Outcomes: A Systematic Review with Meta-Analysis

Dmitriy Viderman,
Fatima Nabidollayeva,
Mina Aubakirova
et al.

Abstract: This study aimed to investigate the efficacy and safety of transcutaneous electrical nerve stimulation (TENS) in postoperative acute pain control. PubMed, Scopus, and Cochrane Library were searched on 1–8 December 2022, for randomized controlled trials on the analgesic effects of TENS. The outcomes were pain intensity and opioid use (primary), and postoperative (PO) adverse events, blood pressure, and the duration of hospital stay (secondary); PROSPERO CRD42022333335. A total of 40 articles were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The Gate Control Theory of pain posits that TENS has the potential to impede the propagation of pain signals to the central nervous system. 19 Moreover, the observed prolonged pain alleviation in our individuals may be attributed to the elevation of endogenous endorphin levels resulting from electrical stimulation. 20 , 21 , 22 , 23 , 24…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The Gate Control Theory of pain posits that TENS has the potential to impede the propagation of pain signals to the central nervous system. 19 Moreover, the observed prolonged pain alleviation in our individuals may be attributed to the elevation of endogenous endorphin levels resulting from electrical stimulation. 20 , 21 , 22 , 23 , 24…”
Section: Discussionmentioning
confidence: 69%
“…The results of our study indicated that TENS therapy has substantial impact on reducing the occurrence of wound infections, expediting wound healing, alleviating pain and enhancing overall patient satisfaction after the Caesarean section. 18 , 19 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%